The Hushed Voices of Autism Chronicling Social and Academic Experiences in College - Cagaanan, Judith S. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2016)
The number of students with autism (SWA) attending college has increased along with the growth of autism diagnoses in recent times. Individuals with autism, despite very strong potential academic advancement, often fail in college. Also, research on the academic and social life of college students with autism has been sparse.. (American Psychiatric Association, 2013). The purpose of this study is to explore the lived experiences of students with autism in Mindanao State University-Iligan Institute of Technology (MSU - IIT), one of the biggest state universities in the Philippines thereby contributing to the existing literatures on autism and understanding SWAS better. Using semi-structured interviews to gather data and exploring the superordinate themes of academic and social life, this study hoped to address the following issues: 1) what is the academic performance of students with autism (SWA) who have sought a college degree in MSU IIT; 2) what are the reported social experiences of these students?; and (3) what possible support program can be provided to help these students? Through phenomenological analysis, insights provided by participants revealed that autistic college students in MSU- IIT have the strong potential to succeed in their academic pursuits, but continually struggle with social issues that threaten to sustain their academic performance. Overall, results indicate the need for institutions of higher education like MSU - IIT to provide comprehensive supports, most importantly, in the social and emotional domains for students with autism (SWA) to succeed in academic environments.